Peningkatan oral and mental activities melalui model problem based learning - Rizqi Fitriani (Jurnal Pendidikan Profesi Guru, 2021)
Penelitian ini memiliki tujuan untuk menunjukkan peningkatan Oral activities and Mental activities melalui model pembelajaran Problem Based Learning. Siswa tidak mau bertanya, siswa belum mampu mengemukakan pendapat, dan menyampaikan kesimpulan. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK) dilaksanakan pada bulan September 2020 hingga Maret 2021. Subyek penelitian ini adalah peserta didik kelas IVB SDN Mojorejo 1 Batu sebanyak 15 siswa. Pengambilan data menggunakan instrument lembar wawancara, lembar observasi, dokumentasi. Lembera observasi digunakan untuk menganalisis Oral activities and Mental activities melalui model pembelajaran Problem Based Learning. Hasil penelitian menunjukan bahwa terdapat peningkatan Oral activities and Mental activities melalui model pembelajaran Problem Based Learning. Hal ini dibuktikan pada Oral activities siklus I menunjukkan kategori rendah dengan rata-rata sebesar 2,87 dan siklus II mencapai rata-rata 3,18 dengan kategori tinggi. Sedangkan Mental activities siklus I menunjukkan kategori rendah dengan rata-rata sebesar 2,93 dan siklus II mencapai rata-rata 3,27 dengan kategori tinggi. Kesimpulan penelitian ini yaitu penggunaan model pembelajaran Problem Based Learning dapat meningkatkan Oral activities and Mental activities.   Increasing oral and mental activities through problem based learning model. This study aims to show the improvement of oral activities and mental activities through the problem-based learning model. Students do not want to ask questions, students have not been able to express opinions, and convey conclusions. This type of research is Classroom Action Research (PTK) conducted from September 2020 to March 2021. The subjects of this study were 15 students of class IVB SDN Mojorejo 1 Batu. Retrieval of data using the instrument interview sheets, observation sheets, documentation. The observation sheet is used to analyze oral activities and mental activities through the Problem Based Learning learning model. The results showed that there was an increase in Oral activities and mental activities through the Problem Based Learning learning model. This is evidenced in the first cycle oral activities showed a low category with an average of 2.87 and in the second cycle an average of 3.18 with a high category. Meanwhile, the first cycle of mental activities shows a low category with an average of 2.93 and an average of 3.27 in the second cycle. The conclusion of this research is that the use of the Problem Based Learning learning model can improve oral activities and mental activities.